THE INFLUENCE OF LIQUIDITY RATIO, PROFITABILITY RATIO, AND SOLVENCY RATIO ON COMPANY VALUE IN THE PROPERTY AND REAL SECTOR COMPANIES ESTATE IN INDONESIA STOCK EXCHANGE 2016-2017 PERIOD - Redy Herinanto Albertus; Eka Dwi Lestari (UPMI Management, 2022)
This study aims to analyze the partial effect of the Current Ratio (CR), Operating Profit Margin (OPM), and Debt to Equity Ratio (DER) on firm value (PBV). Analyzing the simultaneous effect of the Current Ratio (CR), Operating Profit Margin (OPM), and Debt to Equity Ratio (DER) on firm value (PBV) in property, real estate, and building construction companies in the Indonesia Stock Exchange. The population in this study were all property, real estate, and building construction sector companies listed on the IDX from 2016 to 2017. In comparison, the sample of this study was determined by purposive sampling to obtain 19 sample companies. The type of data used is secondary data obtained from www.idx.co.id. This study uses multiple linear regression analysis to see the effect of each independent variable on the dependent variable. Based on the results of multiple regression analysis with a significance level of 5%, the results of this study conclude, simultaneously, Current Ratio (CR), Operating Profit Margin (OPM), and Debt to Equity Ratio (DER) have a significant effect on firm value (PBV). Partially Current Ratio (CR) and the Debt to Equity Ratio (DER) have a significant effect on firm value (PBV). While the variable Operating Profit Margin (OPM) partially has no significant effect on firm value (PBV). JEL Classification: M20, M41, O16